Nintedanib is Safe and Effective in Patients with IPF: Results of the INPULSIS Trials - Hoyle, Brian (MD Conference Express, 2014)
Nintedanib, a tyrosine kinase inhibitor that targets fibroblast growth factor, platelet-derived growth factor, and vascular endothelial growth factor, was shown to lessen the decline in lung function and decrease acute exacerbations in patients with idiopathic pulmonary fibrosis (IPF) in the Phase 2 TOMORROW study [Richeldi L et al. N Engl J Med 2011]. This article presents the primary results for two 52-week Phase 3 randomized, placebo-controlled trials (Safety and Efficacy of BIBF 1120 at High Dose in Idiopathic Pulmonary Fibrosis Patients [INPULSIS] I and II) [Richeldi L et al. N Engl J Med 2014].